2022
DOI: 10.3390/e24101480
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis Method Based on AUPLMD and RTSMWPE for a Reciprocating Compressor Valve

Abstract: In order to effectively extract the key feature information hidden in the original vibration signal, this paper proposes a fault feature extraction method combining adaptive uniform phase local mean decomposition (AUPLMD) and refined time-shift multiscale weighted permutation entropy (RTSMWPE). The proposed method focuses on two aspects: solving the serious modal aliasing problem of local mean decomposition (LMD) and the dependence of permutation entropy on the length of the original time series. First, by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results revealed that LMD is more suitable and performs better than EMD for the incipient fault detection. Song et al 38 proposed a fault feature extraction method that combines adaptive uniform phase local mean decomposition (AUPLMD) and refined time‐shift multiscale weighted permutation entropy (RTSMWPE) to recognize different categories and severities of reciprocating compressor valve faults. Yang and Zhou 39 utilized LMD and wavelet packet transform (WPT) to extract fault features of a diaphragm pump check valve.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that LMD is more suitable and performs better than EMD for the incipient fault detection. Song et al 38 proposed a fault feature extraction method that combines adaptive uniform phase local mean decomposition (AUPLMD) and refined time‐shift multiscale weighted permutation entropy (RTSMWPE) to recognize different categories and severities of reciprocating compressor valve faults. Yang and Zhou 39 utilized LMD and wavelet packet transform (WPT) to extract fault features of a diaphragm pump check valve.…”
Section: Introductionmentioning
confidence: 99%